A Pre-experimental Study to Assess the Effectiveness of Structured Teaching Program Regarding Knowledge about Home Management of Selected Common Illnesses in Pre-school Children among Mothers Residing in Rural Area of Panipat (International Journal of Nursing Education, 2020)
Background: Child care is mostly responsibility of mothers. Therefore, the mother’s knowledge about child care influences the nature and quality of care that is given to the child. Several studies have revealed that the mother’s level of education has a positive impact on her knowledge and how she deals with child health care issues.Aims: To assess the knowledge about home management of common illness.Method: A one group pre-test post-test pre-experimental design and evaluative approach adopted. The study was conducted among 60 mothers conveniently selected from rural area of Panipat.Result: The results of the study shows that in pre-test, mothers were having poor knowledge 31.66%, Average knowledge 68.34% and good knowledge 0.00% regarding selected common illness of children and mean score was 11.57 in post-test, poor knowledge is 0.00%, average 41.66% and good knowledge is 58.34% regarding selected common illness of children and means score was 20.77, The post-test mean knowledge score is significantly greater than the pre-test mean knowledge score so structured teaching programme was effective.Conclusion: This study concluded that structure teaching programme was highly effective in improving knowledge of mothers about home management of common illness in children.